Predictors of renal function decline in patients with gastroenteropancreatic neuroendocrine tumors undergoing [177Lu]Lu-DOTA-TATE therapy - Felix L. Herr; Christian Dascalescu; Victoria Fusch; Caroline Smith; Ricarda Ebner; Mathias J. Zacherl; Florian Eckenweber; Konrad Klimek; Christoph J. Auernhammer; Christine Spitzweg; Jens Ricke; Maurice M. Heimer; et al. (EJNMMI Research)
Abstract Background Peptide receptor radionuclide therapy (PRRT) with [177Lu]Lu-DOTA-TATE is an established treatment for advanced gastroenteropancreatic neuroendocrine tumors (GEP-NETs). While overall renal safety is high, the kidneys remain an organ at risk. This study aimed to determine whether clinical parameters can predict the risk of PRRT-associated renal function decline. Results This retrospective single-center study included 178 patients with well-differentiated GEP-NETs (Grade 1 or 2) who completed four cycles of [177Lu]Lu-DOTA-TATE between 2012 and 2023. Mean baseline eGFR was 81.1 ± 16.3 mL/min/1.73 m² and remained stable at follow-up (81.1 ± 17.8 mL/min/1.73 m², p = 0.989). A KDIGO-defined renal function decline (eGFR follow-up to baseline ratio < 0.8) was observed in 15 patients (8.9%). Higher age at baseline was significantly associated with increased risk (OR: 1.07, 95% CI: 1.01–1.14, p = 0.023), while baseline eGFR (OR: 1.03, 95% CI: 0.99–1.06, p = 0.1) and estimated renal radiation dose (eRRD) (OR: 1.06, 95% CI: 0.89–1.21, p = 0.456) were not significant predictors. No significant associations were found for preexisting renal disease, arterial hypertension, diabetes mellitus, or nephrotoxic drugs. ROC analysis yielded an AUC of 0.683 for age, identifying 68.77 years as the optimal threshold for risk stratification of CKD-progression free survival. Conclusions While the overall risk of renal function decline following [177Lu]Lu-DOTA-TATE therapy of GEP-NET patients is low, age at baseline emerged as a simple yet clinically meaningful predictor of renal function decline in this cohort.